Factors-Factors Causing Occurrence of asphyxia neonatorum In Newborn Regional General Hospital RokanHulu - HERAWATI, RIKA (Jurnal Martenity and Neonatal, 2013)
Asphyxianeonatorumisa state ofthebabyis not breathingspontaneouslyandregularlysoonafter birth. According to WHO(World Health Organisation)in 2002 showedthat27% ofnewborn deathcaused byasphyxianeonatorum.The purposeof this researchisknowingthe factorsthat causeasphyxianeonatorumin newbornsin hospitalsRokanHuluin 2011.